Kontaminasi Escherichia coli pada Minuman Kekinian di Pusat Kota Kabupaten Mamuju - Islam, Fahrul; Ahmad, Haeranah; Saddania, Sitti (LPPM Hang Tuah Pekanbaru, 2024)
The increasing popularity of contemporary drinks has led to the proliferation of contemporary beverage outlets in Indonesian society, including in the city center of Mamuju Regency. Unhygienic and sanitary management can cause bacterial contamination in drinks which can result in health problems. This study aims to identify the bacteriological presence of Escherichia coli (E. coli) in contemporary beverages within the downtown area of Mamuju District to prevent diseases associated with E. coli content that do not comply with regulations. The research method uses an observational method with a descriptive approach. Examination of E. coli bacteria in contemporary drinks uses the Most Probable Number (MPN) method which consists of a presumptive test and a confirmed test. Sampling used a purposive sampling approach by taking samples from 11 contemporary beverage traders with permanent shops and 11 contemporary beverage traders with container shops in the city center of Mamuju Regency. This research was carried out in June-September 2023. Results: Out of 11 beverage samples from container stalls, 91% (n=10) tested positive and 9% (n=1) tested negative for the presence of E. coli, while in permanent stall types, 73% (n=8) tested positive and 27% (n=3) tested negative for the presence of E. coli. Conclusion: The majority of contemporary beverages circulating in the downtown area of Mamuju District tested positive for containing E. coli bacteria. The presence of E. coli in food and beverages indicates inadequate sanitation levels and suggests the possibility of contamination by human feces, thus potentially causing various gastrointestinal diseases. Suggestion: It is advisable to conduct E. coli bacteria testing up to confirmation testing. Regular and programmed monitoring of the hygiene and sanitation of contemporary beverages should be undertaken by the Health Agency.